Investigation of Luminescence Characteristics of SrLaGa3O7:Dy3+ Phosphors. (29th December 2020) - Yang, Yu-Guo; Li, Zhi-Jian; Zuo, Xiang-Gang; Zhang, Rui; Wang, Xu-Ping; Li, Qing-Gang; Liu, Bing; Lv, Xian-Shun; Wei, Lei; Zhang, Yuan-Yuan
Abstract : We synthesized Dy 3+ doped SrLaGa3 O7 phosphors via a sintering process at 1350 °C under atmosphere. The X-ray diffraction data demonstrate that they have the pure tetragonal phase, meaning the successful substitution of Dy 3+ in SrLaGa3 O7 host. Monitoring at 572 nm, Dy 3+ doped SrLaGa3 O7 phosphors show a series of excitation bands within 275–475 nm. Exciting at 342 nm, Dy 3+ doped SrLaGa3 O7 phosphors show emission bands in the range of 450–700 nm. The emission bands respectively locate in blue, yellow and right light regions, which respectively correspond to 4 F9/2 → 6 H15/2, 4 F9/2 → 6 H13/2 and 4 F9/2 → 6 H11/2 transitions of Dy 3+ . The concentration quenching is induced by dipole-dipole interactions among neighboring Dy 3+ ions. There is only one peak in the thermoluminescence glow curves of Dy 3+ doped SrLaGa3 O7 phosphors, indicating that there is only one type of trap center in these phosphors. The trap depth is calculated to be 0.754 eV.